Once upon a time : a story collection - Hale, Shannon (New York : Little, Brown and Co., 2014)
"A new chapter is about to begin at Ever After High, and all students are preparing to return to school and start their Legacy Year, when they will commit to living out their fairytale destinies, repeating the famous stories of their parents"--Provided by publisher.
5.0
3-6.
3-6
Keywords: Characters and characteristics in literature -- Juvenile fiction; Fairy tales; Characters in literature -- Fiction; Fairy tales; Characters and characteristics in literature -- Fiction; Fairy tales; JUVENILE FICTION / Fairy Tales & Folklore / General; JUVENILE FICTION / Media Tie-In.; JUVENILE FICTION / Short Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Toys, Dolls, Puppets; Fairy tales